1987
DOI: 10.1002/jctb.280390108
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of spent hydrodesulphurisation (HDS) catalyst in low pressure distillate hydrocracking—a case study

Abstract: A BS TRA CT Low pressure hydrocracking (40-80 atm., 425°C and 0.5 liquid hourly space velocity is achieved economically on a low cost spent hydrodesulphurisation catalyst (cobalt-molylalumina) using vacuum distillate of Indian crudes. Once through, conversion to products boiling below 371°C was in the range 40.69-43.04 wt % with the middle distillate amounting to 32.03-38.24 wt %.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…In some studies, the spent catalysts were rst decoked before reused and were found to have good activity and selectivity for mild hydrocracking of vacuum distillates to middle distillates. 40,41 A comprehensive review of the recycling of spent HDS catalysts can be referred. 42 The hydrocracking activity was determined by analyzing the simulated distillation results of the liquid products, as shown in Fig.…”
Section: Catalyst Reusability and Hydrocracking Activitymentioning
confidence: 99%
“…In some studies, the spent catalysts were rst decoked before reused and were found to have good activity and selectivity for mild hydrocracking of vacuum distillates to middle distillates. 40,41 A comprehensive review of the recycling of spent HDS catalysts can be referred. 42 The hydrocracking activity was determined by analyzing the simulated distillation results of the liquid products, as shown in Fig.…”
Section: Catalyst Reusability and Hydrocracking Activitymentioning
confidence: 99%